An umbrella of dominance? An examination of oppressive beliefs in the context of rape - Hockett, Jericho M. (Kansas State University, 2009)
Research has demonstrated that negative perceptions of rape victims may vary based on characteristics such as the victims’ race (e.g., Estrich, 1987; Wyatt, 1992). This study examined rape from feminist (e.g., Collins, 1991; hooks, 2003) and Social Dominance Theory (SDT; e.g., Pratto, 1996; Sidanius, 1993) perspectives to assess the relationship between individuals’ social dominance orientation (SDO) and differences in their attitudes toward rape victims of differing races. After reading newspaper-style vignettes describing the rape of either a White or Black victim, participants (N = 83) completed measures assessing their levels of rape myth acceptance (RMA), gender role beliefs, SDO, racism, and social desirability. Results indicated that participants’ SDO scores significantly predicted their perceptions of the triviality of the rape. Specifically, when participants’ SDO scores were higher, they perceived the rape as less trivial for White victims. However, participants higher in SDO did not perceive the rape of Black victims as being either more or less trivial. Consistent with previous research, this study also found that negative attitudes toward women significantly predicted overall negative perceptions of both the Black and White rape victims (e.g., Hockett, Saucier, Hoffman, Smith, & Craig, in press) and that individuals perceived the Black rape victims as less credible than the White rape victims (Wyatt, 1992). These results contribute to our understanding of the relationships among individuals’ attitudes about power, race, and rape by offering support for feminist theories about the relationship between rape and power, as well as for SDT and feminist theories regarding the structure of dominance.
Keywords: Attitudes toward rape victims; Racial attitudes; Social dominance orientation; Feminist theory; Individual differences; Perceptions of rape victims; Psychology, Social (0451)